Effect of microwave technology and upcycled orange fibre on the quality of gluten-free muffins. (15th March 2022) - Rodríguez, Raquel; Alvarez-Sabatel, Saioa; Ríos, Yolanda; Rioja, Patricia; Talens, Clara
Abstract: The objective of this study was to analysis of the impact on the quality of gluten-free muffins of the application of two baking technologies (microwave (MW) and conventional oven (CO)) and the incorporation of two citrus fibres (MF - fibre obtained by the combination of hot air and microwave drying and CF – commercial fibre). Height measurement, instrumental texture and sensory analyses (Quantitative Descriptive Analysis and preference) were performed. Results showed that the height of MW muffins was higher than when CO was applied. The MW reduced the hardness and chewiness regardless of the fibre used, obtaining MF-MW muffins with similar hardness to the CF-CO. The MF muffins presented a more convex appearance and a slightly more intense orange internal colour regardless of the baking technology used. Consequently, the use of MW and the MF resulted in a potential combination for the development of gluten-free products with improved sensory properties. Highlights: The quality impact of microwave and conventional baking technologies was compared. The impact of two citrus fibres on the quality of gluten-free muffins was compared. The physical and sensory properties of muffins were compared. Microwave and new fibre allowed developing improved quality gluten-free muffins.